Mind-Reading Ability and Structural Connectivity Changes in Aging - Cabinio, Monia; Rossetto, Federica; Blasi, Valeria; Savazzi, Federica; Castelli, Ilaria; Massaro, Davide; Valle, Annalisa; Nemni, Raffaello; Clerici, Mario; Marchetti, Antonella; Baglio, Francesca (Frontiers in Psychology, 2015)
The Mind-Reading ability through the eyes is an important component of the affective Theory of Mind (ToM), which allows people to infer the other’s mental state from the eye gaze. The aim of the present study was to investigate to which extent age-associated structural brain changes impact this ability and to determine if this association is related to executive functions in elderly subjects. For this purpose, Magnetic Resonance Imaging was used to determine both gray matter and white matter areas associated with aging. The resulting areas have been included in a subsequent correlation analysis to detect the brain regions whose structure was associated with the Mind-Reading ability through the eyes, assessed with the Italian version of the “Reading the Mind in the Eyes” (RME) test, in a sample of 36 healthy subjects ranging from 24 to 79 years of age. The analysis resulted in three important findings: 1) the performance to the RME test is relatively stable across the decades 20-70 (despite a slight decrease of this ability with aging) and independent from executive functions; 2) structural brain imaging demonstrated the involvement of a great number of cortical ToM areas for the execution of the RME test: the bilateral precentral gyrus, the bilateral posterior insula, the left superior temporal gyrus and the left inferior frontal gyrus, which also showed a significant volume decrease with age; 3) an age and task-related decline in white matter connectivity on left fronto-temporal portion of the brain. Our results confirm the age-related structural modifications of the brain and show that these changes have an influence on the Mind-Reading ability through the eyes.